“BULUNG SANGU” (GRACILARIA VERRUCOSA) LOW COST BALINESE SEAWEED PRODUCT, NUTRITION, GENERAL AND ORODENTAL HEALTH (A REVIEW) - I Gusti Ayu Ari Agung; I Gusti Ngurah Alit Wiswasta; I Nengah Sudja (Unmas Press, 2019)
In Bali, several types of seaweed are generally consumed as low-cost vegetables or salad by the local people and known by local names of jukut and rujak bulung sangu. Jukut and rujak bulung sangu is a very harmonious combination of food, a potential source of nutrients, and antioxidants. Therefore, this study was conducted to review nutrition, general and rodental health benefits of bulung sangu. Bulung sangu have potential nutrient and antioxidants content such as carotenoids, vitamins (A,C,E), fatty acids (omega 3 and 6), carbohydrates, minerals (I, Zn, Fe, Cu, Na, K, Mg, Ca, P and Cr), amino acid and chlorophyll. Carotenoids have an important biological function as an antioxidant and immunostimulatory which can prevent diseases, antiinflammatory, antistress, antiaging, and protect the skin from the harmful effects of ultraviolet radiation. The results of several research stated that total karotenoids and iodium is higher in bulung sangu, and that has significant potency as antistress, anticancer, antiinflammatory, antistroke and antipathogenic bacteria. They also have significant roles as normolipidemic, antidiabetic, antiatherosclerotic, antiosteoporotic, antiaging, and orodental health. The conclusion is that the jukut and rujak bulung sangu is high in nutrients and antioxidants, has the potential to maintain general health as well as orodental health